Should consent forms used in clinical trials be translated into the local dialects? A survey among past participants in rural Ghana. (April 2016) - Baiden, Frank; Akazili, James; Chatio, Samuel; Achana, Fabian Sebastian; Oduro, Abraham Rexford; Ravinetto, Raffaella; Hodgson, Abraham
Background: Obtaining informed consent is part of the expression of the principle of participant autonomy during clinical trials. It is critical that participants understand the content of informed consent forms and remain in a position to seek independent advice on its content. We conducted a survey among past participants of a clinical trial in the Kassena-Nankana Districts of rural northern Ghana about the usefulness of informed consent forms that are written in the local dialects. The written forms of local dialects are largely undeveloped. Method: We contacted a randomly selected sample of caregivers whose children were enrolled in a completed clinical trial and interviewed them using a structured questionnaire. Analysis sought to determine participants' preference and whether or not they were likely to find confidants who will be able to read, understand and give advice on the content of the informed consent form to them when they take the informed consent forms home. Results: We interviewed 394 caregivers, 88.6% of whom were women. About half (54%) of the respondents wanted the informed consent forms to be in the English language. Caregivers with higher than primary level education were more likely to prefer the informed consent form to be in English than those with no formal education (74% versus 26%, p = 0.04). The majority (85%) indicated that they would be able to find close confidants who would be able to read and explain it to them if it is in English. In contrast, only 8% thought they would be able to do the same if the informed consent form was written in the local language. Respondents were more likely to find close confidants to read and explain the informed consent form if it were written in English than if it were written in the local language (94% versus 19%, p value < 0.01). Conclusion: The practice of translating informed consent forms into undeveloped local dialects and giving such copies to trial participants to send home needs to be re-evaluated. In populations where the written forms of local dialects are undeveloped and literacy is low, the use of local dialect versions of informed consent forms could ironically enhance the vulnerability of trial participants.